Factors associated with increased burnout in genetic counseling students. - McCormick, Halle; Wetherill, Leah; Oehlman, Laura; Delk, Paula (Journal of Genetic Counseling, 2025)
Genetic counseling students face numerous stressors during their graduate program, which can lead to negative outcomes such as burnout. Burnout can negatively impact students' ability to perform well, maintain stamina, and feel competent throughout their training. The Maslach Burnout Inventory (MBI) is a validated survey that assesses three domains that together define burnout: exhaustion, cynicism, and low self‐efficacy. One hundred eighty genetic counseling students from the classes of 2024 and 2025 within the United States and Canada completed a cross‐sectional, quantitative survey which included the MBI validated for students, a list of 19 situations tailored to students in genetic counseling training programs that may cause stress, and three open‐ended questions asking what activities helped reduce stress, including resources provided by the program and resources students would like to be provided. Genetic counseling students endorsed an average of nine situations that caused them "some" or "a lot" of stress. Results revealed that 12% of current students met criteria for having burnout (defined as high exhaustion, high cynicism, and low self‐efficacy); an additional 20% met criteria for two of the three burnout subscales. The most consistent predictors of burnout were the numbers of situations causing a student stress and being in the latter part of training. Thematic analyses revealed that personal activities, social activities, and mental health services helped reduce stress, while support in relation to academics was a desired resource. This study reveals that burnout is experienced by genetic counseling students and is associated with factors such as having a high number of situations causing a student stress or being more than halfway through the graduate program. These results provide insight into areas and methods for genetic counseling graduate programs to attenuate burnout in their students.